Implementation of International Law and Standards on Civil Aviation in the Republic of Azerbaijan - Naftaliyeva, Dilara (ADA University, 2020)
Ratifying the Convention on International Civil Aviation, the Republic of Azerbaijan has obliged to implement the provisions of this Convention and Standards and Recommended Practices (SARPs) of the International Civil Aviation Organization (ICAO) into the national legal system. After the ratification of Convention on International Civil Aviation, the legislative framework in the field of civil aviation has considerably improved and within the judicial reforms, have been adopted laws, regulations, state programs, and other normative legal acts in the field of civil aviation. But despite these reforms, the SARPs in the civil aviation field is continuously changing by the reason of development the civil aviation industry from time to time, which makes important the ongoing implementation of them into the national legal system of Contracting States. The lack of appropriate legislation in the field of civil aviation leads to the ineffective fulfillment of the international obligations by the Republic of Azerbaijan under international law. Since the non implementation of the Standards and Recommended Practices of ICAO to national legislation lead to the findings during the audits and monitoring conducted by the ICAO. If the national legislation is not in compliance with the international standards and recommended practices of ICAO, the provision of aviation security and flight safety cannot comply with international standards and consequently, the results of international audits and inspections, monitoring and internal audits cannot be successful. Generally speaking, the lack of effective implementation of SARPs into national legislation and its implementation in the civil aviation industry, may directly or indirectly cause accidents and serious incidents in civil aviation, the prevention which is the main responsibility of the Member States. Analyzing the current legislation in civil aviation, I have reveal that the international standards and recommended practices of ICAO have not comprehensively implemented to our national legal system and the policy maker should make a decision on how to incorporate them effectively. This is a crucial issue because the international obligation of Azerbaijan in front of ICAO should be executed by the government. The decision which the policy maker decide on, has not only legal but also political and diplomatic importance for the Republic of Azerbaijan. We can generalize that, the more effective implementation of international law and standards into national legislative acts, will lead to the full transportation of the Convention provisions and Standards in civil aviation into national legal system. In other words, the analyzed legislation, scientific articles, audit results and other available resources allow us to generalize that the implementation of international law and standards on civil aviation in the Republic of Azerbaijan is the significant way in holding high level of aviation security and flight safety.
Keywords: Public and International Affairs; ICAO -- Standards.; National and International legislation -- Azerbaijan.; International Civil Aviation Organization.